The National Integrated Project for Prospective Observation of Non-communicable Disease and its Trends in the Aged 2010 (NIPPON DATA2010): Objectives, Design, and Population Characteristics - Aya Kadota; Nagako Okuda; Takayoshi Ohkubo; Tomonori Okamura; Nobuo Nishi; Hirotsugu Ueshima; Akira Okayama; Katsuyuki Miura (Journal of Epidemiology, 2018)
Background: The structure and risk factors for cardiovascular diseases (CVD) in Japan may change because lifestyle, particularly nutrition, socioeconomic status, and medical care, which affect CVD, may markedly change over time. Therefore, a new prospective cohort study on a representative general Japanese population based on national surveys is required. Methods: In November 2010, the baseline survey of the National Integrated Project for Prospective Observation of Non-communicable Disease and its Trends in the Aged 2010 (NIPPON DATA2010) was performed with the National Health and Nutrition Survey of Japan (NHNS2010) in 300 randomly selected districts throughout Japan. The survey included a questionnaire, electrocardiogram, urinalysis, and blood biomarkers added to the NHNS2010 examinations. Physical measurements, blood biomarkers, and dietary data were also obtained in NHNS2010. Socioeconomic factors were obtained by merging with the Comprehensive Survey of Living Conditions 2010 (CSLC2010) dataset. Participants are followed annually for the incidence of diabetes mellitus, CVD events (acute coronary events, heart failure, atrial fibrillation, and stroke), and cause-specific mortality. The activities of daily living are followed every 5 years. Results: A total of 2,898 individuals aged 20 years or older agreed to participate in the baseline survey of NIPPON DATA2010. The participation rate was 74.6%. Of these, data from NHNS2010 was merged for 2,891 participants (1,236 men and 1,655 women). The data of 2,807 participants were also merged with CSLC2010 data. Conclusions: We established NIPPON DATA2010 as a cohort study on a representative general Japanese population that covers all of Japan.